Deficiency of tissue inhibitor of matrix metalloproteinase-1 (TIMP-1) impairs nutritionally induced obesity in mice - Roger Lijnen, H.; Demeulemeester, Diego; Van Hoef, Berthe; Collen, Désiré; Maquoi, Erik (Thrombosis and Haemostasis, 2003)
Tissue inhibitor of matrix metalloproteinase-1 deficient (TIMP-1–/–) mice and wild-type (TIMP-1+/+) controls were kept on a standard (SFD) or a high fat diet (HFD) for 15 weeks. At the time of sacrifice, TIMP-1–/– mice on HFD had a significantly lower body weight (29 ± 1.5 versus 41 ± 1.8 g, p <0.005), and significantly less subcutaneous (0.81 ± 0.19 versus 1.78 ± 0.21 g, p <0.05) and gonadal (0.87 ± 0.17 versus 1.85 ± 0.18 g, p <0.005) fat mass. These differences were much less pronounced for mice on SFD. On HFD but not on SFD, adipocyte diameters were significantly lower in the adipose tissue of TIMP-1–/– mice. Plasma leptin levels in TIMP-1–/– mice on HFD were significantly lower as compared to TIMP-1+/– mice, and strongly correlated with adipose tissue mass for both genotypes. Staining with an endothelial cell specific lectin revealed a significantly higher blood vessel density, larger stained area and vessel size in adipose tissue of TIMP-1–/– mice on HFD. This difference disappeared after normalization to the adipocyte number, suggesting that it does not represent a true enhancement of angiogenesis. Thus, in a murine model of nutritionally induced obesity, TIMP-1 promotes adipose tissue development.
Keywords: Tissue inhibitor of metalloproteinase-1; TIMP-1; adipose tissue; obesity; angiogenesis